CONCEPT OF THE DEVELOPMENT OF DECISION SUPPORT IN EMERGENCY - O.V. OLKHOVIK; A.A. PETRIKIN; I.V. BOGUSLAVSKIY (Advanced Engineering Research)
A conceptual model of the computer-aided decision support system in an emergency situation at the machine-building plant is discussed in the article.